Enhanced recovery after laryngectomy: A feasibility study in 25 patients. Issue 12 (December 2022) - Magos, Tiarnan; Massa, Gabriella; Burdett, Edward; Al Khalfan, Abdulla; Thaj, Jabin; Al Yaghchi, Chadwan; Ali, Safina
Purpose: To describe the development and implementation of an enhanced recovery programme for patients undergoing total laryngectomy. Methods: A feasibility study set in a tertiary head and neck unit in London, United Kingdom. The programme was developed based on Enhanced Recovery After Surgery (ERAS) Society guidelines for head and neck cancer surgery and local expert group consensus. An ERAS 'booklet' was devised which accompanied all laryngectomy patients during their inpatient stay. Contributors included otolaryngologists, anaesthetists, dieticians, physiotherapists, speech and language therapists and nurses. A 12-month pilot study was undertaken. The main outcome measures were feasibility and adherence. Results: An enhanced recovery programme for 25 people undergoing total laryngectomy was successfully piloted in a tertiary referral head and neck unit. Median length of stay was reduced in the post-ERAS group by 1.5 days. No statistically significant difference in length of stay, time to first gastrografin swallow, rate of fistula nor postoperative normalcy of eating between the pre and post-ERAS patients who underwent laryngectomy was observed. Clavien-Dindo-grouped complication rates were significantly higher in the post-ERAS group. Conclusion: This enhanced recovery programme for patients undergoing laryngectomy is the first of its kind in the literature. Implementation has been demonstrated feasible. Further longitudinal studies are required to reliably inform us on ERAS programmes' effects on laryngectomy outcomes.